ENT300 : Fundamental Of Entrepreneurship Wase's Homemade Burger Company Business Plan / Wynder Bradder Anak Hosen... [et.al] - Hosen, Wynder Bradder; Mohd Jaya, Alif Akhmizan; Maraka, Elvin; Jegelah, Sudan Natalia (2015)
We have decided to register our business under partnership. It is because our business is consisting of four members. So, our business is incorporated under the Business Registration Act 1956 (Amendment 1978). We are going to open business of which we have chooses homemade burger, French fries and drink as our product. All partners in our company are having their own roles such as general manager, administrative manager, marketing manager, operation manager and financial manager. So each partner in our company is entitled to actively participate in the management of the business. This can make sure that our business run smoothly based on our planning and also can help us in order to achieve our goal. The relationship between the entire partners also important to make sure that we can work together to achieve our vision and goal. In our company, there will be one of our partner holding two posts as general manager and administrative manager since he has experiences opening business before and good in both. Besides that, all partners also have their own right to make any decision in daily routine in our business and usually all the changes should be agreed by majority of members. This can help our company to increase our products and services according to the market demand to ensure we can achieve our target and goals effectively and efficiency.